New place, new opportunities - article Editorial (Разработка и регистрация лекарственных средств)
In February 2023, the opening of the laboratory complex of LLC "Center for Pharmaceutical Analytics" took place in the building at 8 Simferopol Boulevard. In connection with the relocation of the laboratory, the Russian federal television channel "NTV" released a report where the general director of LLC "CPHA" gave an interview about the current activities of the company and prospects.